2018
DOI: 10.3390/risks6020061
|View full text |Cite
|
Sign up to set email alerts
|

On Exactitude in Financial Regulation: Value-at-Risk, Expected Shortfall, and Expectiles

Abstract: This article reviews two leading measures of financial risk and an emerging alternative. Embraced by the Basel accords, value-at-risk and expected shortfall are the leading measures of financial risk. Expectiles offset the weaknesses of value-at-risk (VaR) and expected shortfall. Indeed, expectiles are the only elicitable law-invariant coherent risk measures. After reviewing practical concerns involving backtesting and robustness, this article more closely examines regulatory applications of expectiles. Expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 137 publications
(90 reference statements)
0
15
0
1
Order By: Relevance
“…VaR function is stretched on all figures twice to the left of point 1  to compare it with other functions as in [7,14,16].…”
Section: Fx  mentioning
confidence: 99%
“…VaR function is stretched on all figures twice to the left of point 1  to compare it with other functions as in [7,14,16].…”
Section: Fx  mentioning
confidence: 99%
“…A look at past studies in finance literature shows that, as opposed to other models, Value at Risk can be calculated much more accurately, using the EVT (Gencay and Selcuk 2004;Omari et al 2017). However, VaR is not only incoherent but also fails to precisely estimate the risk of loss when the loss distributions show "fat tails" (Rockafellar and Uryasev 2002), and this significantly hurts the accuracy of this risk measure (Chen 2018). Kourouma et al (2010) investigated the VaR and the Expected Shortfall during the 2008 financial crisis, and showed that VaR, as opposed to CVaR, underestimated the risk of loss, while the conditional EVT model performed more accurately.…”
Section: Research Backgroundmentioning
confidence: 99%
“…It is therefore important to model these price fluctuations and implement an effective tool for managing energy price risk. VaR has become a popular risk measure in the financial industry among many other alternative risk measures (e.g., [3,4]). The internal model approach under the Basel II framework proposes VaR as a risk measure to gauge the amount of assets needed to cover possible losses, that is, the minimum regulatory capital requirements.…”
Section: Literature Reviewmentioning
confidence: 99%